2005
DOI: 10.1091/mbc.e04-04-0295
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Versican V1 and V2 Isoforms in Cell Proliferation and Apoptosis

Abstract: Versican is a large chondroitin sulfate proteoglycan belonging to the lectican family. Alternative splicing of versican generates at least four isoforms named V0, V1, V2, and V3. We have shown that the versican V1 isoform not only enhanced cell proliferation, but also modulated cell cycle progression and protected the cells from apoptosis. Futhermore, the V1 isoform was able to not only activate proto-oncogene EGFR expression and modulate its downstream signaling pathway, but also induce p27 degradation and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
147
2
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(165 citation statements)
references
References 36 publications
14
147
2
2
Order By: Relevance
“…When the expression of versican isoforms was determined with specific primers, mainly V1 was found to contribute to this upregulation, whereas V2 expression was not induced. This observation is consistent with previous reports that demonstrated that versican isoforms V1 and V2 are not only differentially expressed, but also play distinct roles in cell function which are mediated by GAG-a and GAG-b domains, respectively (Wu et al, 2004b;Sheng et al, 2005). The balanced expression of these two isoforms might provide a suitable extracellular environment for normal proliferation and survival of cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…When the expression of versican isoforms was determined with specific primers, mainly V1 was found to contribute to this upregulation, whereas V2 expression was not induced. This observation is consistent with previous reports that demonstrated that versican isoforms V1 and V2 are not only differentially expressed, but also play distinct roles in cell function which are mediated by GAG-a and GAG-b domains, respectively (Wu et al, 2004b;Sheng et al, 2005). The balanced expression of these two isoforms might provide a suitable extracellular environment for normal proliferation and survival of cells.…”
Section: Discussionsupporting
confidence: 92%
“…The balanced expression of these two isoforms might provide a suitable extracellular environment for normal proliferation and survival of cells. The extracellular environment might become favourable for cell proliferation and survival when V1 expression is increased, as in the case of tissue development and tumour formation (Sheng et al, 2005). Recently, in parallel to our results in high-grade gliomas, TGF-b2 was reported to trigger the expression of V0/V1 and hyaluronan in osteosarcoma cells (Nikitovic et al, 2006).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These data are consistent with evidence that formation of versican-hyaluronan pericellular matrix is required for SMC proliferation and migration (Evanko et al 1999). Versican V1 may enhance proliferation via increased levels of the EGF receptor and ERK activation coupled with loss of the cell-cycle inhibitor p27 (unpublished data, Rahmani M, Wong B, Allahverdian S, Cheung C, Carthy J, Keire P, Wight T, McManus B) (Sheng et al 2005). V1 also inhibits 3T3 cell death (Sheng et al 2005).…”
Section: Possible Role Of Versican Breakdown Products In Vascular Dissupporting
confidence: 80%
“…Overexpression experiments suggest that versican V1 stimulates cell proliferation, whereas versican V2 inhibits proliferation (Sheng et al 2005). The converse experiments using antisense or siRNA also indicate that endogenous versican V1 increases proliferation, including that of SMCs , Huang et al 2006) (unpublished data, Rahmani M, Wong B, Allahverdian S, Cheung C, Carthy J, Keire P, Wight T, McManus B).…”
Section: Possible Role Of Versican Breakdown Products In Vascular Dismentioning
confidence: 99%